A Case of Giant Right Coronary Artery Aneurysm after DES Implantation (Cardiovascular Journal, 2022)
Coronary artery aneurysms (CAAs) are not very uncommon but giant coronary artery aneurysms are rare with a reported prevalence of 0.02% to 0.2%. Recently, with the advent of implantation of drugeluting stents, there are increasing reports suggesting stents causing coronary aneurysms, months or years after the procedure. Though most of the CAAs are asymptomatic, they may present with various clinical presentations like angina pectoris, fistula formation, pericardial tamponade, compression of surrounding structures, congestive cardiac failure or sudden death. The natural history and prognosis remain unclear. Despite the important anatomical abnormality of the coronary artery, the treatment options of CAAs are still poorly defined and present a therapeutic challenge. We report a case of iatrogenic giant CAA following percutaneous transluminal coronary angioplasty (PTCA) with its relevant management strategy.Cardiovasc j 2022; 15(1): 88-94